PEMBERDAYAAN MASYARAKAT DALAM MENINGKATKAN KEMAMPUAN KEPEMANDUAN WISATA DI DESA WISATA CIBUNTU KAB. KUNINGAN PROVINSI JAWA BARAT - Fajri, Khoirul; Kartika, Titing; Afriza, lia (Universitas Djuanda, 2020)
Desa Cibuntu (Cibuntu Village) is a tourism-based village located at the foot of Mount Ciremai, Pasawahan District, Kuningan, West Java. The village is located approximately 20 KM from the center of Kuningan City. Cibuntu Village has a variety of uniqueness that is owned both in nature, culture and history. Cibuntu Village is declared as a Tourism Village as stipulated in the Decree of the Head of the Kuningan District Tourism and Culture Office Number 55631 / KPTS.178.A Disparbud / 2012 concerning the designation of Cibuntu Village as an Object and Attraction (Tourism Village). Guiding tours become very important because they are part of the service. Lack of communication skills and mastery of English become the main obstacle in guiding tourism activities in the Cibuntu Tourism Village. The people who are assigned as guides seem to only have capital, so the delivery of information is not packaged properly to tourists. Referring to these conditions, then the solution is coaching and mentoring in an effort to improve the ability to guide tours through a series of training. The training will be classified into two categories, namely tour guides and English training for tour guides. The methods to be used include lectures, questions and answers, discussions. To improve the ability to guide in English will focus on drilling models and role play. As targets to be achieved are (a) increasing the ability of understanding the role of the tour guide, (b) increasing the ability of the community in the tour guide, (c) increasing the ability of English in guiding activities especially when guiding foreign tourists, (d) increasing communication skills when guide the tour. To achieve these targets the activity implementation team will work together with the association of Indonesian tour guides and professional guides.